The 6 month interim analysis of a randomized controlled trial assessing the quality of life in patients with breast cancer related lymphedema undergoing lymphaticovenous anastomosis vs. conservative therapy - Y. M. J. Jonis; J. A. G. N. Wolfs; S. Hummelink; H. J. P. Tielemans; X. H. A. Keuter; S. van Kuijk; D. J. O. Ulrich; R. R. W. J. van der Hulst; S. S. Qiu (Scientific Reports, 2024)
Abstract Breast cancer related lymphedema (BCRL) is a chronic condition with a detrimental impact on psychosocial and physical well-being. Lymphaticovenous anastomosis has shown promising results in alleviating physical symptoms and increasing quality of life in patients with BCRL. The aim of the study is to evaluate the effect on health related quality of life (HrQol) after LVA surgery versus conservative treatment in patients with BCRL. The study is a prospective, multicenter randomized controlled trial. Adult women with unilateral BCRL, with early stage lymphedema and viable lymphatic vessels were included. The primary outcome measure was HrQol measured by the lymphedema functioning disability and health (Lymph-ICF) questionnaire. The secondary outcomes were volume difference measured by the water displacement method; the Upper Extremity Lymphedema (UEL) index; and daily use of the compression garments after 3 and 6 months. For this interim analysis 46 patients per group were included. There was a significant improvement in the domains in physical and mental function in the Lymph-ICF questionnaire in the LVA group after 6 months, (− 16.46 ± 18.5, p < 0.05, − 10.12 ± 29.5, p < 0.05 respectively). However, there was no statistical difference in the total score of the Lymph-ICF after 6 months in both groups (LVA-group; − 8.57 ± 22.6, p > 0.05, CDT-group; − 2.65 ± 18.2, p < 0.05). Furthermore, there was no significant volume reduction in both groups (LVA-group: 20.04 ± 196.40, p = 0.497, CDT: 33.98 ± 189.87, p = 0.236). In the LVA group, 41% partially of completely stopped wearing the compression garments after six months whereas in the CDT group 0% discontinued to use of compression garments. LVA resulted in improvement of the domains physical and mental function of the Lymph-ICF. Limb volume did not significantly improve after 6 months. However, around 42% could completely or partially stopped with the use of compression garments in the LVA group. The current results are promising, however longer follow up is required to assess long term effect of LVA for secondary lymphedema. Clinical Trial Registration: NCT02790021 registered on 03/06/2016